Immunolocalization and quantitation of avian lipoprotein lipase - George, Ian M. R. (The University of Edinburgh, 1993)
The overall aim of the project was to investigate the pools of LPL activity that exist within chicken tissues in vivo. Polyclonal and monoclonal anti-chicken LPL antibodies were produced using highly purified chicken adipose tissue LPL as an immunogen. An attempt was made to measure LPL at the luminal surface of the capillary endothelium of individual tissues using an iodinated antichicken LPL monoclonal antibody, injected intravenously, in vivo.However, the technique was not successful because high levels of specific antibody binding were not achieved.Heparin-release studies using the isolated perfused heart model system found significant species differences, between rats and chickens, in the regulation of heparin-releasable LPL in response to fasting. The low percentage of heparin-releasable LPL activity observed in chickencardiac tissue corresponded to the relatively low accumulation oftriacylglycerol NEFA by the chicken muscular tissues by comparisonwith adipose tissue, following the intravenous injection of [^4C]-VLDL invivo. Using anti-chicken LPL antibodies immunocytochemical studies on a variety of chicken extrahepatic tissues showed the enzyme to be located predominantly extracellularly, at the basement membrane of the tissue parenchymal cells and in association with the interstitial capillary elements. Image-analysis was used to quantify the pools of enzymeassociated with these compartments in chicken cardiac tissue. In chicken bone marrow LPL was found in association with the adipocytes and vascular elements of the marrow mass, with a lack of enzyme associated with the haematopoietic cells. Immunocytochemical techniques were also used to investigate the tissue specific developmental changes which occur in the distribution of LPL during the growth and maturation of the heart and liver of the embryonic chicken. The present study has identified several pools of LPL within chicken tissues and proposed that the transportation of enzyme from the interstitial capillary elements to the luminal endothelial surface may play a role in the regulation of functional LPL activity in chicken tissues.
The immunolocalization and quantitation of avian lipoprotein lipase